1997
DOI: 10.1002/(sici)1096-9861(19971006)386:4<613::aid-cne7>3.0.co;2-5
|View full text |Cite
|
Sign up to set email alerts
|

Synaptic plasticity of 5-hydroxytryptamine-immunoreactive terminals in the phrenic nucleus following spinal cord injury: A quantitative electron microscopic analysis

Abstract: The present study was conducted to examine the plasticity of 5-hydroxytryptamine (5-HT)-immunoreactive terminals in the rat phrenic nucleus following an ipsilateral C2 spinal cord hemisection and 30-day survival period. A retrograde horseradish peroxidase (HRP) labeling technique was used to identify the phrenic motoneurons at the electron microscopic (EM) level. After employing a pre-embedding immunocytochemical technique, the ultrastructural characteristics of 5-HT-immunoreactive terminals were qualitatively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(20 citation statements)
references
References 64 publications
2
18
0
Order By: Relevance
“…Examination of serotonin-labeled terminals using electron microscopy, before and after C2 hemisection (30 days), revealed that the number of serotonin immunoreactive terminals contacting phrenic motor neurons was significantly elevated in hemisected rats (77). Moreover, depletion of serotonin significantly attenuated the morphologic changes induced by C2 spinal hemisection (78).…”
Section: Synaptic Strengthening Onto Phrenic Motoneuronsmentioning
confidence: 98%
“…Examination of serotonin-labeled terminals using electron microscopy, before and after C2 hemisection (30 days), revealed that the number of serotonin immunoreactive terminals contacting phrenic motor neurons was significantly elevated in hemisected rats (77). Moreover, depletion of serotonin significantly attenuated the morphologic changes induced by C2 spinal hemisection (78).…”
Section: Synaptic Strengthening Onto Phrenic Motoneuronsmentioning
confidence: 98%
“…This form of time-dependent plasticity following chronic spinal hemisection has been called the "crossed phrenic phenomenon" and is one of the longest known examples of plasticity in respiratory motor control (83,196). Spontaneous enhancement of crossed spinal pathways to phrenic motoneurons is serotonin dependent (85,86,228). Similarly, depression of respiratory motor output in the phrenic nerve contralateral to hemisection requires serotonergic neurons (74).…”
Section: Injury-induced Respiratory Plasticitymentioning
confidence: 99%
“…16,17,31,84 Replacement synaptic growth may originate from both spinal interneurons and from primary segmental afferents. 16,17,[85][86][87] A postulated signal for new synaptic growth is the increase in NTs caudal to a SCI.…”
Section: Clinical Descriptionmentioning
confidence: 99%